Pengaruh DER, ROE dan EPS terhadap Harga Saham Perusahaan Konstruksi dan Bangunan di BEI - Refi Maulida Sari; Iwan Setiawan; Diharpi Herli Setyowati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The problem in this research is the decline stock prices of Construction and Building Companies when infrastructure development projects are intensively implemented. This study aims to determine the effect of DER, ROE, and EPS on the Stock Prices of Construction and Building Companies on the IDX in 2014-2019. The research method uses an associative type of quantitative method with a population of Construction and Building Companies on IDX 2014-2019 and obtained a sample of 8 companies taken through purposive sampling technique. The study was conducted using multiple linear regression analysis with the help of SPSS software version 25. The results show that simultaneously DER, ROE, and EPS have a significant effect on Stock Prices. Partially DER and EPS have a positive and significant effect on Stock Prices while ROE has no positive and significant effect on Stock Prices.